Inward rectifier potassium (Kir) channels mediate salivary gland function and blood feeding in the lone star tick, Amblyomma americanum. - Zhilin Li; Kevin R Macaluso; Lane D Foil; Daniel R Swale (Public Library of Science (PLoS), 2019)
BACKGROUND:Tick feeding causes extreme morbidity and mortality to humans through transmission of pathogens and causes severe economic losses to the agricultural industry by reducing livestock yield. Salivary gland secretions are essential for tick feeding and thus, reducing or preventing saliva secretions into the vertebrate host is likely to reduce feeding and hinder pathogen life cycles. Unfortunately, the membrane physiology of tick salivary glands is underexplored and this gap in knowledge limits the development of novel therapeutics for inducing cessation of tick feeding. METHODOLOGY:We studied the influence of inward rectifier potassium (Kir) channel subtypes to the functional capacity of the isolated tick salivary gland through the use of a modified Ramsay assay. The secreted saliva was subsequently used for quantification of the elemental composition of the secreted saliva after the glands were exposed to K+ channel modulators as a measure of osmoregulatory capacity. Lastly, changes to blood feeding behavior and mortality were measured with the use of a membrane feeding system. PRINCIPAL FINDINGS:In this study, we characterized the fundamental role of Kir channel subtypes in tick salivary gland function and provide evidence that pharmacological inhibition of these ion channels reduces the secretory activity of the Amblyomma americanum salivary gland. The reduced secretory capacity of the salivary gland was directly correlated with a dramatic reduction of blood ingestion during feeding. Further, exposure to small-molecule modulators of Kir channel subtypes induced mortality to ticks that is likely resultant from an altered osmoregulatory capacity. CONCLUSIONS:Our data contribute to understanding of tick salivary gland function and could guide future campaigns aiming to develop chemical or reverse vaccinology technologies to reduce the worldwide burden of tick feeding and tick-vectored pathogens.